2013
DOI: 10.26421/qic13.1-2-4
|View full text |Cite
|
Sign up to set email alerts
|

Multiqubit entanglement of a general input state

Abstract: Measurement of entanglement remains an important problem for quantum information. We present the design and simulation of an experimental method for an entanglement indicator for a general multiqubit state. The system can be in a pure or a mixed state, and it need not be ``close'' to any particular state. The system contains information about its own entanglement; we use dynamic learning methods to map this information onto a single experimental measurement which is our entanglement indicator. Our method does … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(39 citation statements)
references
References 15 publications
1
38
0
Order By: Relevance
“…In general the amount of additional training diminishes with increasing size, which raises hopes for the applicability of our technique to systems even of hundreds of qubits. The exception was in the training from three qubits to four (possibly for symmetry reasons -we saw this phenomenon also with the entanglement indicator [17]), though even here, the initial error for the fourqubit calculation was a tenth the size when starting from the three-qubit functions, compared with starting from scratch. And, while direct training by symmetry occurs along a pathway whose progress is not experimentally accessible, we have shown that it is possible to specify a pathway along which the average spin is nonzero and thus checkable.…”
Section: Discussionmentioning
confidence: 66%
See 4 more Smart Citations
“…In general the amount of additional training diminishes with increasing size, which raises hopes for the applicability of our technique to systems even of hundreds of qubits. The exception was in the training from three qubits to four (possibly for symmetry reasons -we saw this phenomenon also with the entanglement indicator [17]), though even here, the initial error for the fourqubit calculation was a tenth the size when starting from the three-qubit functions, compared with starting from scratch. And, while direct training by symmetry occurs along a pathway whose progress is not experimentally accessible, we have shown that it is possible to specify a pathway along which the average spin is nonzero and thus checkable.…”
Section: Discussionmentioning
confidence: 66%
“…For large N, we expect the W states to bootstrap more easily than the GHZ states, because in that limit, the coupling probably only needs to be nearest neighbor. Our earlier work [17] seems to show that for pairwise functions in N qubit systems, there is exponentially less training necessary to go from (N-1) to N qubits, but we have yet to do these calculations on the annealed systems.…”
Section: Learning the W Statementioning
confidence: 99%
See 3 more Smart Citations